Tilawah Art Learning As Motivation Moves Moroccans in Tanjung Bonai District Tanah Datar - Sekar Harum Pratiwi; Fitri Alrasi; Vini Wela Septiana; Nurul Fakhrin; Ismail Syakban (LPPM UIKA Bogor, 2023)
Community service activities carried out for students in the Jorong Gunuang Ledang and Jorong Piabuh environments have received great enthusiasm, both from the surrounding community and parents. From the beginning of operations to direct practice. Given the importance of Qur'anic education for childhood, it reminds us of the most fundamental stage in a child's personal development. Not only about the procedures for completing the learning stages, but also about the quality of reading according to the rules of memorization that will come, understanding the meaning of the Qur'an, and instilling the values of the Qur'an in the child's heart. The method used in participatory learning can essentially be understood as a learning method that involves students optimally in learning activities. This learning focuses on the involvement of students in learning activities, not on teacher dominance in the delivery of student material. In this PKM activity, the focus is on fostering interest in learning and reading the Quran students, by carrying out maghrib reciting activities every night in Jorong Gunuang Ledang and Jorong Piabuh. Understanding the Qur'an is the duty of every Muslim. Allah gives reason and mind to man whose sole purpose is to make man think of what Allah has sent down everything in the universe. One of them is the Qur'an which is used as a guideline for life by Muslims.